Myoepithelial Carcinoma of the Breast with Focal Rhabdoid Features. Issue 1 (17th December 2012) - Ohtake, Hiroya; Iwaba, Akiko; Kato, Tomoya; Ohe, Rintaro; Maeda, Kunihiko; Matsuda, Mikio; Izuru, Kazuhiko; Morimoto, Kazuhiro; Katagiri, Shigeru; Yamakawa, Mitsunori
Abstract Myoepithelial carcinoma of the breast is extremely rare and only 33 cases have been reported in the English literature. Herein, we report a case of myoepithelial carcinoma of the breast with focal rhabdoid features. The patient was a 67‐year‐old woman, who presented with a lump of the left breast that rapidly grew to 3 cm in diameter within 3 months. Lumpectomy revealed a solid and whitish colored tumor, which was composed mainly of elongated spindle‐shaped cells with mild atypia, focal necrosis, and infiltrative margin. In a small area of the lesion, ovoid tumor cells exhibited eccentric nuclei with centrally located nucleoli and plump cytoplasm including round eosinophilic inclusions, resembling a rhabdoid tumor. Immunohistochemically, both types of tumor cells exhibited a myoepithelial phenotype. MIB‐1 index was 30%. The cytoplasmic inclusion of the ovoid cells exhibited immunopositivity for both vimentin and cytokeratin. From these findings, this tumor was diagnosed as a myoepithelial carcinoma with focal rhabdoid features. Although rhabdoid features have been reported in some types of malignant and benign tumors, this is the first report of such features in myoepithelial carcinoma of the breast.